فنون مهارة الاستماع فى القرآن ودورها فى تعلم أربع المهارات اللغوية - Ghofur, Abdul; Rizki, Restu Budiansyah (Program Studi Pendidikan Bahasa Arab, 2023)
Hearing sense which in a study of Arabic language known as maharah al-istima' is one of language art that cannot be separated in learning four language skills which include: listening skill, speaking skill, reading skill, and writing skill. Its presence inside human beings participates in having urgency and complex roles and it is dominants to be developed especially in the learning domain. Moreover, if the listening skill is synergized with other language skills collectively and simultaneously. This article reflects on a specific language in the concept of hearing sense urgency in the perspective of Holy Qur'an of learning language skill, remember that learning skill in a Holy Qur'an as The Scholars opinions are mentioned 27 times earlier than other skills. The perspective theory of hearing sense according to Holy Qur'an in this study then connected to the language learning theory from Scientific Expert. The nature of the connectivity then gave an interesting view which led to functional concept of hearing sense position and its role in learning four languages.